HUBUNGAN ANTARA PERILAKU SOSIAL DAN HASIL BELAJAR DALAM MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) PADA SISWA KELAS V MI - Syaifuddin, Afdillah; Syailin Nichla Choirin Attalina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the relationship between social behavior and learning outcomes in the Natural and Social Sciences (IPAS) subject among fifth-grade students of MI Miftahul Falah Banyumanis Jepara in the 2024/2025 academic year. The research employed a quantitative approach with a correlational design. The population as well as the research sample consisted of 26 students, selected using a saturated sampling technique. Data on social behavior were collected through a Likert-scale questionnaire covering the dimensions of cooperation, tolerance, empathy, and social communication, while data on IPAS learning outcomes were obtained from students’ report card records. Data analysis included descriptive statistics and Spearman’s rho correlation test. The results showed that students’ social behavior was predominantly in the high and very high categories, whereas IPAS learning outcomes were mainly in the high category. The Spearman’s rho correlation analysis yielded a coefficient of 0.997 with a significance level of p < 0.001, indicating a very strong and statistically significant positive relationship between social behavior and IPAS learning outcomes. These findings suggest that the better the students’ social behavior, the higher the IPAS learning outcomes they achieve. Keywords: Cooperation, Social Communication, Learning Outcomes, Social Behavior, Tolerance, Empathy.